2023
DOI: 10.1002/mar.21817
|View full text |Cite
|
Sign up to set email alerts
|

The influence of frontline employee self‐disclosure about products in a retail store on customer trust in the retailer in the context of service encounters

Abstract: The current research investigates how customers respond to self‐disclosure by frontline employees in the service encounter context of retailing. Three scenario‐based experiments demonstrate that self‐disclosure by frontline employees related to the promoted products in a retail store has a beneficial impact on the trust which customers feel in the store. This effect is mediated by both perceived employee effort and intimacy toward employees. However, this self‐disclosure effect is mitigated when customers perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
(149 reference statements)
0
1
0
Order By: Relevance
“…Given such attribution processes, customers may be open to marketing communications that highlight a digital companion's characteristics—particularly, shared characteristics as they increase attractiveness (Byrne et al, 1967) and goal‐relevant attributes as they indicate an agent's capabilities to effectively support customers’ consumption processes (Arndt et al, 2021). In support of this, research in an offline context has shown that customers feel greater intimacy with frontline employees who share personal experiences related to the promoted products with them (Park & Yi, 2023).…”
Section: Hypotheses Developmentmentioning
confidence: 98%
“…Given such attribution processes, customers may be open to marketing communications that highlight a digital companion's characteristics—particularly, shared characteristics as they increase attractiveness (Byrne et al, 1967) and goal‐relevant attributes as they indicate an agent's capabilities to effectively support customers’ consumption processes (Arndt et al, 2021). In support of this, research in an offline context has shown that customers feel greater intimacy with frontline employees who share personal experiences related to the promoted products with them (Park & Yi, 2023).…”
Section: Hypotheses Developmentmentioning
confidence: 98%